Efektifitas Metode Diskusi Dalam Meningkatkan Hasil Belajar Siswa Kelas VII Pada Mata Pelajaran PKn Di MTs Nurul Karomah Kecamatan Galis Kabupaten Bangkalan - Moh Supriyanto Zakaria; Ernawati; Soubar Isman (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
This study aims to determine the effectiveness of discussion learning methods in improving student learning outcomes in Civic Education subjects in class VII MTs Nurul Karomah. This research method uses descriptive qualitative research. The object of this study was students of MTs Nurul Karomah, Paterongan Village, Galis District, Bangkalan Regency. The sample of this study was grade VII MTs Nurul Karomah Galis District Bangkalan with a total of 73 students. Data analysis was performed using the lesson plan implementation sheet, student activity observation sheets, student response questionnaires and learning achievement tests. The results of the study of the implementation of the RPP on learning Civics using the discussion method carried out very well with the results of the percentage of 78.75. Student activities during the discussion learning took place said to be in a very good category with the achievement of a scale of 78.75. Questionnaire responses of students earned 88.3 means that students gave very positive responses to learning using the discussion method. This means that the activities carried out by students are classified as effective or the learning that has been carried out is able to stimulate students to actively learn in class by using learning discussion methods. Student learning outcomes that have been achieved after a test with KKM 75 using learning methods of discussion are said to be effective because the number of students who complete reaches a percentage of 94.44%. The conclusion from the research that has been done, that the discussion learning method in MTs Nurul Karomah Galis sub-district of Bangkalan district has been effective in improving student learning outcomes in PPKn subjects. This can be seen the teaching and learning process carried out by Civics teachers and the learning outcomes achieved by students both and have increased.